1986
DOI: 10.1016/s0022-5347(17)45783-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Prostatic Carcinoma with D-Trp-6-LH-RH: Plasma Hormone Levels After Daily Subcutaneous Injections and Periodic Administration of Delayed-Release Preparations

Abstract: The hormonal effects of a delayed-release intramuscular (IM) preparation of D-Trp-6-LH-RH (Decapeptyl microcapsules) were investigated in men aged 65-75 years. Six men with a prostatic adenoma (group A) received subcutaneously (SC) 500 p g DecapeptyUday for seven days. Seven men with a prostatic carcinoma (group B) were given the same SC treatment, but in addition received on days 8, 28, and 56 an IM injection of Decapeptyl microcapsules. During SC treatment, plasma Decapeptyl levels rose to 2-4 ng/ml. Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We have demonstrated that the microcapsules are much more efficacious than multiple daily injections [7,32,33]. The efficacy of D-Trp-6-LHRH microcapsules in the treatment of advanced prostatic carcinoma was demonstrated in animal experiments and in clinical trials [31,34,35]. However, a limitation to the use of LHRH agonists alone is the transient increase in serum testosterone, resulting from augmented secretion of lutein-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the microcapsules are much more efficacious than multiple daily injections [7,32,33]. The efficacy of D-Trp-6-LHRH microcapsules in the treatment of advanced prostatic carcinoma was demonstrated in animal experiments and in clinical trials [31,34,35]. However, a limitation to the use of LHRH agonists alone is the transient increase in serum testosterone, resulting from augmented secretion of lutein-…”
Section: Discussionmentioning
confidence: 99%
“…Since 1983, we have been developing sustained delivery systems for peptides. These systems are based on microcapsules or microgranules of DL-lactide-co-glycolide, which are biodegradable and compatible with living tissues [33,34]. Our pharmaco-kinetic study of the release pattern of SB-75 from microcapsules demonstrated that during the therapeutically important continuous phase, the liberation of only a small amount of the peptide is required to maintain a complete suppression of the pituitary-gonadal axis in rats [41].…”
Section: Serum Testosterone Levels In Rats Injected With the Lh-rh Anmentioning
confidence: 93%
“…The results of Roger et a1 [ 181 and Parmar et al [ 191 in men with prostate cancer attest to the high clinical efficacy of once a month administration of microcapsules of suppressing testosterone secretion. The accumulated results [1][2][3][4][5][6][7]18,19] reinforce the view that long-term therapy with agonists of LH-RH is a viable alternative to surgical castration or therapy with estrogens in men with metastatic prostate cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Roger and coworkers 51 provided evidence for the efficacy of periodic administration of Decapeptyl microcapsules for suppressing testicular secretion in patients with prostate cancer. Each patient received an intramuscular injection equivalent to 3 mg Decapeptyl in microcapsules designed to deliver, in a controlled fashion, a daily dose of 100 µg D-Trp 6 LHRH for 30 days.…”
Section: Prostate Cancermentioning
confidence: 99%